The Neutrophil-to-Lymphocyte Ratio as A Noninvasive Marker in Patients with Biopsy-Proven Non-Alcoholic Steatohepatitis - Mehmet Asıl; Ramazan Dertli (İstanbul Medical Journal, 2016)

(untitled)
Objective: Non-alcoholic fatty liver disease is a global health problem with an increasing prevalence. The neutrophil-to-lymphocyte ratio is a cheap inflammatory parameter that can be easily calculated from routine complete blood count tests. This study was designed to investigate the neutrophil-to-lymphocyte ratio in patients with non-alcoholic steatohepatitis and simple hepatosteatosis.Methods: Fifteen patients with biopsy-proven non-alcoholic steatohepatitis, 65 patients with simple steatosis diagnosed with abdominal ultrasound, and 65 healthy controls were included. Anthropometric measurements were obtained during a routine physical examination. The neutrophil-to-lymphocyte ratio was calculated from routine complete blood count tests, and its relationship with various clinical and laboratory parameters was analyzed.Results: The mean neutrophil-to-lymphocyte ratio was 2.16±0.49 in the patients with non-alcoholic steatohepatitis, 1.62±0.43 in the patients with simple steatosis, and 1.51±0.31 for healthy controls; the difference among the groups of patients were statistically significant (p<0.001). A paired analysis revealed that patients with non-alcoholic steatohepatitis had a significantly higher neutrophil-to-lymphocyte ratio than patients with simple steatosis and healthy controls, whereas the difference between the latter two groups of patients was not statistically significant. The neutrophil-to-lymphocyte ratio was not associated with the degree of steatosis on performing abdominal ultrasound and with histological findings of liver biopsies (p>0.05). ROC analyses for the neutrophil-to-lymphocyte ratio to differentiate patients with steatohepatitis revealed an AUC of 0.868 (95% CI: 0.781–0.956) and 86.5% sensitivity and 81% specificity for the selected cut-off value of 1.793.Conclusion: The results of this study showed that the neutrophil-to-lymphocyte ratio was higher in patients with steatohepatitis than in patients with simple steatosis and healthy controls. Taking into account that the difference between patients with simple steatosis and healthy controls was not statistically significant, the increased neutrophil-to-lymphocyte ratio in the patients with steatohepatitis can be attributed to a low level of systemic inflammation accompanying the hepatic inflammation.